Performance of Legislative Budgeting Institutions on Government Institutions in North Maluku - Runtunuwu, Prince Charles Heston; Tussabaha, Aisah (AIBPM Publisher, 2020)
The purpose of this study is to analyze the influence of the role of DPRD budgeting function and organizational commitment on the potential for fraud. This type of research is quantitative research. The sampling technique used is non-probability sampling using the saturated sampling method. The data used are primary data using a questionnaire. Data was successfully collected from 40 respondents who were members of the DPRD Kota Ternate, Tidore Islands City and Sula Islands District. The data processing technique used is multiple linear regression with the help of SPSS. The results showed that there was no influence on the role of the DPRD's budgeting function on the potential for fraud in district / city DPRDs in North Maluku Province, there was a positive and significant effect on organizational commitment to potential fraud in the budget bodies of the DPRD districts / cities of North Maluku province. In addition, the simultaneous statistical test shows that the role of the DPRD budgeting function and organizational commitment has a significant effect on the potential for fraud among members of the DPRD budgeting in North Maluku province.